Evaluación del clima organizacional y su incidencia en el desempeño laboral de los colaboradores del Instituto de Educación Superior Tecnológico Privado Amazónico de la ciudad de Tarapoto, provincia y región San Martín. 2013 - Águila Cárdenas, Delia Nike Del (2013)
Nowadays the organizations establish within their policies the analysis of the organizational climate, seeking with that the employee develops in a suitable working environment to reach one of the objectives that every company pursues that is the productivity. The organizational climate and the work performance are determined by the way the staff judges their activity in the institution, although the collaborators usually seek different objectives when they decide to provide their services, they consider that to achieve productivity it is indispensable that they feel satisfied with the Work climate prevailing in that organization. That is why most people consider that if they enjoy a high-level work environment, it contributes to the success of the company in a significant way. The mere fact of carrying out their work is often insufficient, if their work, does not allow them to influence the decisions that affect them. Consequently, today's leaders and professionals are united in the need to create in the organization a climate and a good performance, in which people are truly treated as responsible experts in their positions. The organizational climate and the work performance are integrated by different elements, of which, some of them will be analyzed, according to the organizational context, due to the particular characteristics that the organization presents. Conscious of the above, our research has contemplated the need to carry out a research study and analysis of some of these factors that are related to the organizational climate and the work performance so that necessary implementations can be made in this institution. Therefore, this research intends that based on the results of the diagnosis of the organizational climate and the work performance can identify the characteristics and elements susceptible of being oriented to the achievement of the goals and objectives of the organization. Also, our research has as central axis the correlation that exists between the organizational climate with the labor performance and the determination of the characteristics that intervene in the labor environment of the collaborators of the Institute of Higher Education Technological Amazonia Private. The use of the climate and performance questionnaire allowed us to demonstrate that the institute presents a significant direct relationship between organizational climate and work performance. In turn, this process means that the employees have a good job performance